Cu2O cubic and polyhedral structures versus commercial powder: Shape effect on photocatalytic activity under visible light - Fernando Plascencia-Hernández; Ana L. Luna; Christophe Colbeau-Justin; Patricia Santiago; Miguel Garcia-Rocha; Guadalupe Valverde-Aguilar; Miguel A. Valenzuela (Journal of Saudi Chemical Society)
A simple precipitation-reduction method was used to prepare cubic and polyhedral Cu2O structures. Their morphological, structural, optical and electronic properties were analyzed and compared with those of commercial Cu2O by means of SEM, TEM, XRD, UV–vis DRS, Photoluminescence Spectroscopy and Time Resolved Microwave Conductivity. Methyl orange (MO) photodegradation with visible light (blue-light LEDs, λ = 450–470 nm) was taken as a model reaction to study the photocatalytic activity. According to the results, Cu2O edge-and corner-truncated polyhedral particles significantly decreased the MO initial concentration by adsorption and photocatalysis, whereas, Cu2O cubic particles did not show MO adsorption but slightly higher photocatalytic activity than the polyhedral particles. Commercial Cu2O showed MO adsorption and high electron mobility but it was completely inactive. These results were explained in terms of the crystalline defects that influence both, the adsorption capacity and the photocatalytic activity. Keywords: Cu2O, Morphology, Photocatalysis, Photoluminescence, TRMC